ECONOMIC EFFICIENCY OF ENERGY-EFFICIENT CONSTRUCTION - Kharit Oleg Michailovich, (International Journal of Innovative Technologies in Social Science, 2024)
Energy efficiency plays a crucial role in the modern development of the construction sector, as it helps reduce energy costs and lower the negative impact on the environment. Under the conditions of global climate change and growing demand for energy resources, the issue of energy efficiency is becoming more and more relevant. The study aims to assess the effectiveness of implementing energy-efficient technologies in US buildings. As a result of the study, it has been established that energy efficiency is a key factor for reducing costs and CO₂ emissions, which is especially topical in the context of climate change. Investments in this area provide substantial economic benefits: the average net present value (NPV) for residential buildings is $15,000, while for commercial – $50,000. The internal rate of return (IRR) for residential objects reaches 12% and for commercial – 20%. The payback period for residential buildings is, on average, six years, while for commercial objects, it is only four years. Implementing energy-efficient technologies leads to a significant reduction in energy consumption, which provides savings of $4,200 per year for residential and $24,000 for commercial buildings. The decrease in CO₂ emissions is also substantial, with residential buildings reducing emissions from 50 to 30 tons per year and commercial buildings from 250 to 150 tons, both reductions amounting to 40%. The satisfaction level of residents of residential buildings is 88%, while that of commercial buildings is 92%. Thus, energy-efficient solutions positively affect the economy, ecology, and quality of life.